Medical tourism-A New Arena - S Puri; A Singh; Yashik (Iranian Journal of Public Health, 2010)
Globalisation has given birth to medical tourism. Health and medical tourism are the fastest growing segments in not only developed nations but in developing countries too. India has become a hot destination, as the Indian medical standards match up to the highly prescribed international standards at a very low cost. However, it is an unmixed blessing; along with advantages, it has many unintended side effects also.